Revista radial juvenil web para la Unidad Educativa Salesiana Cardenal Spellman. - Delgado Benavides, Byron Ernesto (2016)
This document is a synthesis of the implementation process carried out at Salesiana Cardenal Spellman School, which was aimed at creating a radio show in a magazine format. The pedagogical model was based on the interactivity generated by the students by means of social relevant contents dealing with teen related problems. The project is divided into three stages, detailing the process: preproduction, production, and postproduction. Where the selection of participants, training, structuring of discourse was made through dialogue for subsequent recording and publication. The autonomous realization of the content to be treated in each episode was discussed based on the various milestones that take place during adolescence, such as: sexuality, culture, politics and social relationships. The results that have been contrasted from the structuring of the youth radio magazine, with the participation of the students involved, in first instance projects, new dynamic communication that became visible, the learning that has led to this joint effort with makers, so the effects of such learning aim on an indirect influence public, as a last resort would be the perfect complement of documented during the process. The substantial influence that provides the radial magazine brings the institution a transcendent way of creating a diverse support communication within the different environments: family, institutional and social.